SAT0613 CHANGING TREATMENTS AND OUTCOMES FOR JUVENILE IDIOPATHIC ARTHRITIS: INITIAL FINDINGS FROM A NEW CANADIAN INCEPTION COHORT. (June 2019) - Guzman, Jaime; Batthish, Michelle; Berard, Roberta; Bolaria, Roxana; Cabral, David; Chédeville, Gaëlle; Duffy, Ciaran; Gerhold, Kerstin; Gerschman, Tommy; Huber, Adam; Proulx-Gauthier, Jean-Philippe; Rosenberg, Alan; et al.
Abstract : Background: Treatments for juvenile idiopathic arthritis (JIA) are changing rapidly. Healthcare providers and families require up-to-date knowledge of current treatment practices and expected outcomes to inform their decisions. Objectives: To assess changes in treatment practices and outcomes for children in a new Canadian inception cohort diagnosed with JIA in 2017-2018, compared to children in the Research in Arthritis in Canadian Children emphasizing Outcomes cohort (ReACCh-Out) diagnosed in 2005-2010 1 . Methods: A new investigator-driven Canadian Alliance of Pediatric Rheumatology Investigators (CAPRI) JIA Registry was started in February 2017 to prospectively collect information on children enrolled within 3 months of JIA diagnosis. Information about disease activity, treatments, outcomes and adverse events is collected at all clinic visits. Registry data were extracted in October 2018 and clinical characteristics at presentation, use of anti-rheumatic medications, attainment of inactive disease, cJADAS10 scores and adverse events were described. Selected findings were compared to those observed in the ReACCh-Out cohort. The proportion of patients (cumulative incidence) receiving various treatments and their outcomes were estimated with Kaplan Meier survival methods. Results: A total of 166 patients enrolled a median of 6 weeks after diagnosis at 10 centres were included. Median age at diagnosis was 9 years (IQR 3, 13), 61% were female and 51% had oligoarthritis. At enrolment, subjects had a median of 2 active joints (IQR 1, 3), a Physician Global Assessment of 3 (1.5, 4) and a Parent Global Assessment of 1 (0, 3). The median cJADAS10 score was 6.5 (4, 10). Table 1 compares baseline characteristics and the cumulative incidence of medication use and inactive disease at one year after diagnosis with those observed in the ReACCh-Out cohort, diagnosed on average 10 years earlier. Figure 1 shows the Kaplan Meier curves for attainment of inactive disease. Conclusion: In Canada, treatments for newly diagnosed patients with JIA have intensified in the last 10 years, and 35% will now start their first biologic within 1 year of diagnosis. Short-term outcomes have improved, 81% of current patients now attaining inactive disease within one year of diagnosis. Funding: The Arthritis Society, Canada. References: [1] Guzman J, Oen K, Tucker LB, et al. The outcomes of juvenile idiopathic arthritis in children managed with contemporary treatments: results from the ReACCh-Out cohort. Ann Rheum Dis.2015;74:1854-60 Acknowledgement: Funding: The Arthritis Society, Canada. Disclosure of Interests: Jaime Guzman: None declared, Michelle Batthish Speakers bureau: Novartis, Abbvie, Roberta Berard: None declared, Roxana Bolaria: None declared, David Cabral: None declared, Gaëlle Chédeville: None declared, Ciaran Duffy: None declared, Kerstin Gerhold: None declared, Tommy Gerschman: None declared, Adam Huber: None declared, Jean-Philippe Proulx-Gauthier: None declared, Alan Rosenberg: None declared, Dax Rumsey: None declared, Heinrike Schmeling Grant/research support from: F. Hoffmann-La Roche Ltd, Natalie Shiff: None declared, Gordon Soon: None declared, Lori Tucker: None declared